Yttrium iron garnet heterocoagulated by silica - Godoi, R. H.M.; Marques, R. F.C. [UNESP]; Varanda, L. C. [UNESP]; Jafelicci, M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2002)
There are several reasons to make to cover magnetic materials with shells of different chemical composition. One is to change physical (optical, magnetic, conductive, etc.) and/or chemical properties of dispersions by choosing the coating material. YIG can show special interest as a magnetic dye, for microwave absorption and as a magnetic fluids when it is coated by another material. Surface and interface magnetic properties are intimately connected with the new properties of the silica on yttrium iron garnet system. Néel first introduced the concept of surface anisotropy and Chen et al. (1998) developed a model that describes the anisotropy effects at the border surface particle, which was applied in this work. Spherical YIG particles were prepared by coprecipitation method and it was coated by silica using the TEOS hydrolysis process. The transmission electron microscopy reveals clearly the edge between silica and yttrium iron garnet. Hysteresis loops shows comparatively the profile of pure and covered YIG. The non-coated samples show the magnetization near to that of the bulk, Ms = 26 emu.g-1, while covered samples present lower values than those obtained for the naked particle. Surface anisotropies were calculated using the Chen et al. model. Domain walls are unflexible when a thin layer covers the magnetic particle, so it is not a surprise that the Ks estimated is reduced by one order of magnitude, as observed in this work. Theoretically, Néel's values of nanoparticle surface anisotropy should be between 0. 1 and 1 erg/cm2 and our data agree with this theory. Surface magnetization is generally lower than the inner one and its effect leads to thermodynamic perturbation in exchange interaction near to the surface, which can be estimated. Indeed, in heterocoagulation systems, the surface anisotropy is a result of the symmetry breaking, as observed.